Chimeric Antigen Receptor T-cells in Kidney Disease - Tangkitchot, Jirapath; Pongsuwan, Karn (Journal of the Nephrology Society of Thailand, 2025)
Chimeric antigen receptor (CAR) T-cells are T-lymphocytes genetically modified to recognize and kill specific antigens on cells, especially cancer cells. This emerging form of immunotherapy is gaining increasing significance in modern medicine. Initially developed to treat hematologic malignancies, CAR T-cell technology has evolved to target a broader range of cancers, including non-hematologic malignancies, as well as kidney-related diseases such as lupus nephritis, HIV-related kidney disease, and renal cell carcinoma. Research on CAR T-cell therapy for these conditions is growing, with more studies involving human subjects. However, as a relatively new therapeutic approach, most available data currently comes from case reports or series. Despite promising outcomes, CAR T-cell therapy can lead to severe complications, underscoring the need for large-scale studies and randomized controlled trials to establish sufficient evidence for its use in patient care.